Carbon Peeling Laser Treatment to Improve Skin Texture, Pores and Acne Lesions: A Retrospective Study - Claudio Conforti; Stefania Guida; Caterina Dianzani; Piergiorgio Turco; Vito Cazzato; Iris Zalaudek; Domenico Piccolo (Medicina, 2022)
Carbon peel laser treatment has been described for the improvement of skin texture, with pore reduction and acne lesion treatment. The technique consists of applying a carbon mask to the face for about ten minutes followed by laser irradiation with a Q-switched 1064 nm laser. This mechanism of action seems to be related to small carbon molecules binding both the corneocytes and serum within the hair follicles; the effect of the laser eliminates carbon bound to skin particles and the high temperature generated reduces sebum production by sebaceous glands and inhibits Cutibacterium acnes replication. Although this method was described 20 years ago, scientific data supporting its efficacy and safety have only recently been reported in small case series. For this reason, we performed a retrospective study including patients treated from January to May 2022 in the context of a private practice. Even if this study is limited by the low number of patients and its retrospective nature, this is the first research to show that carbon peel laser, performed with a standardized technique, is an effective and safe treatment for patients with acne lesions, showing pores and wrinkles, and is able to improve the overall skin aspect.